2022
DOI: 10.1128/msystems.00723-22
|View full text |Cite
|
Sign up to set email alerts
|

Multiple T6SSs, Mobile Auxiliary Modules, and Effectors Revealed in a Systematic Analysis of the Vibrio parahaemolyticus Pan-Genome

Abstract: Gram-negative bacteria employ toxin delivery systems to mediate their interactions with neighboring cells. Vibrio parahaemolyticus , an emerging pathogen of humans and marine animals, was shown to deploy antibacterial toxins into competing bacteria via the type VI secretion system (T6SS). Here, we analyzed 1,727 V. parahaemolyticus genomes and revealed the pan-genome T6SS repertoire of this species, including the T6SS gene clusters, horizontally shared auxiliary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 78 publications
2
25
0
Order By: Relevance
“…S4B ). We then tested the T6SS-mediated delivery of the predicted effector using a previously established T6SS surrogate system in a V. parahaemolyticus RIMD 2210633 derivative strain 29,37 . We found that expression of the predicted effector and immunity proteins from a plasmid in the surrogate attacker strain led to the killing of a parental prey strain lacking the predicted immunity protein ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S4B ). We then tested the T6SS-mediated delivery of the predicted effector using a previously established T6SS surrogate system in a V. parahaemolyticus RIMD 2210633 derivative strain 29,37 . We found that expression of the predicted effector and immunity proteins from a plasmid in the surrogate attacker strain led to the killing of a parental prey strain lacking the predicted immunity protein ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The construction of the V. parahaemolyticus RIMD 2210633 surrogate strain and of the V. parahaemolyticus BB22OP and V. coralliilyticus BAA-450 derivatives was reported previously 29,37 . Briefly, 1 kb sequences upstream and downstream of each gene to be deleted were cloned into pDM4, a Cm R OriR6K suicide plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular determinant that governs V. parahaemolyticus virulence against humans has been identified as a type III secretion system (29,30); the virulence determinant against shrimp was identified as the PirA/B toxin (31). V. parahaemolyticus also harbors T6SSs (32). T6SS1, which is found in most but not in all strains (32), mediates antibacterial toxicity during interbacterial competition by delivering effector repertoires that differ between strains (32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…V. parahaemolyticus also harbors T6SSs (32). T6SS1, which is found in most but not in all strains (32), mediates antibacterial toxicity during interbacterial competition by delivering effector repertoires that differ between strains (32)(33)(34)(35). T6SS1 was investigated in several strains and was shown to be active under warm marine-like conditions (i.e., 3% [wt/vol] NaCl at 30°C) upon surface sensing activation (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation